Interações gene-gene na via de sinalização induzida pela visfatina/NAMPT na farmacogenética da pré-eclampsia - Daniela Alves Pereira (2019)
Preeclampsia (PE) is a major cause of maternal and perinatal morbidity/mortality, and is characterized by pregnancy-induced hypertension and other clinical criteria, including proteinuria. Antihypertensive therapy prolongs gestation and decreases adverse outcomes. However, 40% of pregnant are nonresponsive to antihypertensive therapy and associated with adverse outcomes. Abnormal placentation and placental ischemia occur in PE, followed by the release of soluble tyrosine kinase-1 (sFLT-1) and soluble endoglin, which leads to low nitric oxide (NO) bioavailability and results in endothelial dysfunction. Visfatin/Nicotinamide phosphoribosyltransferase (NAMPT) favors endothelial NO production, and is a potential biomarker of endothelial dysfunction. In this study, we examined correlations between the plasma levels of visfatin/NAMPT, nitrite (marker of endogenous NO formation), sFLT-1 and ADMA in 205 pregnant with PE (including responsive and nonresponsive to antihypertensive therapy) and 203 of control group, whether NAMPT and VEGF polymorphisms affect plasma nitrite levels, and characterized gene-gene interactions. Genotypes were determined by Taqman allelic discrimination assays. Plasma nitrite levels were measured by ozone-based chemiluminescence assay, and visfatin/NAMPT, sFLT-1 and ADMA by ELISA, which were analyzed by Spearman’s correlation tests. Gene-gene interactions were characterized using Multifactor Dimensionality Reduction. In pregnant with PE, visfatin/NAMPT levels were negatively correlated to nitrite (r=-0.257, 95% CI=-0.477/-0.007, P=0.038), and positively correlated to sFLT-1 (r=0.326, 95% CI=-0.084/0.532, P=0.007). In the control group, visfatin/NAMPT were positively correlated to nitrite levels (r=0.317, 95% CI=0.110/0.497, P=0.002) and negatively correlated to sFLT-1 (r=-0.340, 95% CI=-0.592/-0.027, P=0.029). In the subgroup of PE who are nonresponsive to antihypertensive therapy, visfatin/NAMPT and nitrite levels were negatively correlated (r=-0.376, 95% CI=-0.643/-0.026, P=0.031), and the TC+CC genotypes of NAMPT polymorphisms rs1319501 were associated with low levels of plasma nitrite. We found interactions between genotypes of NAMPT rs1319501 and VEGF rs2010963 polymorphisms when compared control group and PE (P=0.001), and between genotypes of NOS3 VNTR 27pb and VEGF rs2010963 polymorphisms when compared subgroups of PE who were responsive and nonresponsive to antihypertensive therapy (P=0.013). Our findings suggest an inhibitory effect of the visfatin/NAMPT on NO formation in PE and in the subgroup of pregnant with PE who are nonresponsive to antihypertensive therapy. Moreover, our findings suggest that gene-gene interactions in the NAMPT pathway may affect both the susceptibility to PE and the responsiveness to antihypertensive therapy in PE.